CRITERIA OF MANAGERIAL INFLUENCE IN THE CONTEXT OF CONTEMPORARY CHALLENGES TO ORGANIZATIONAL EFFECTIVENESS IN UKRAINE (Development Service Industry Management, 2025)
The article examines the development of a scientifically grounded approach to identifying the priority criteria of managerial influence as a key factor in enhancing organizational effectiveness under conditions of contemporary uncertainty in Ukraine. The authors propose to conceptualize managerial influence as a multidimensional system that encompasses both formal (structural, technological) components and informal (psychological, communicative) aspects, which significantly impact decision-making processes, employee motivation, and the organization’s adaptability to external challenges.The study conducts a systematic categorization of the criteria of managerial influence, enabling their division into four thematic groups: structural-spatial, dynamic, socio-organizational, and strategic-behavioral. Each group reflects specific characteristics of influence that determine not only the quality of managerial decisions but also their capacity to adapt to changes in both internal and external environments. Particular emphasis is placed on analyzing the interrelationships among the pace of change, the nature of innovation implementation, and the level of employee engagement, thereby contributing to the formation of a comprehensive model for assessing managerial influence.The primary objective of the research is not only to classify these criteria but also to identify the mechanisms of their interaction in the context of the modern challenges faced by Ukrainian organizations. The proposed methodology is aimed at optimizing the decision-making process by establishing a hierarchy of criteria that allows managerial influence to be effectively adapted to the specific operating conditions of enterprises during both crisis and stabilization periods.The results obtained hold significant practical potential for developing balanced management strategies aimed at ensuring organizational flexibility and adaptability in a dynamic environment. The proposed conceptual model may serve as a basis for further empirical research and contribute to the development of standardized methods for measuring the effectiveness of managerial influence across various sectors of the Ukrainian economy.
Keywords: managerial influence; organizational effectiveness; management criteria; adaptability; crisis management